The university in transition - Perkins, James Alfred, 1911-1998 (Stafford Little lectures, 1966)
Dr. Perkins' lectures analyze and prescribe the role of the modem university in relation to its faculty and students, to the growth, transmission, and application of knowledge, and to society at large. This persuasive and seminal work will have far-reaching influence on American education. Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.